Across the Border: Push-Pull Dynamics and the Lived Experiences of Nepalese Labour Migrants in India - Bhatt, Deepak Chandra (KMC Journal, 2025)
This study explores the enduring yet under-researched phenomenon of labour migration from Nepal’s Sudurpashchim Province to India, shaped by poverty, underdevelopment, and an open border. Despite its large scale, this migration remains informal and largely undocumented, receiving limited attention in academic and policy arenas. To address this research gap, the study explores the socio-economic and psychological dimensions of the migration process through qualitative methods. These include narrative inquiry, in-depth interviews, key informant interviews, participant observation and case studies. The fieldwork is conducted at the primary border checkpoints of Sudurpaschim Province, specifically at Gaddachowki in Kanchanpur district and Gourifanta in Kailali district. The findings highlight a predominance of male migrants especially from marginalized caste groups, driven by chronic poverty, unemployment, environmental challenges and lack of opportunities at home. Remittances are primarily used to meet basic household needs rather than for long-term development. Due to its informal and undocumented nature, this migration provides immediate financial relief but fails to bring about significant socio-economic transformation. Moreover, limited financial literacy and the absence of institutional support further constrain the potential benefits. The study concludes that labour migration from Sudurpashchim is largely a survival strategy rooted in structural inequalities. It emphasizes the need for comprehensive policy reforms, including bilateral labour, agreements between Nepal and India, social security measures, rural development initiatives, legal awareness campaigns and community-level support systems. Such interventions are crucial to ensure safer, more dignified and informed migration experiences for Nepalese workers.